(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The care and study of medical and social problems of the health status of women of reproductive age is the most important task of the state and public health. These problems need to be addressed nationwide, but at the same time, specific tasks to improve their health should be identified and addressed within each region, taking into account the actual situation on the ground [22,1,9,12]. Platelet pathologies and DVS syndrome that occur during pregnancy threaten not only the mother, but also the child’s organism. Reduces the quality of life, reduces life expectancy, increases the number of disabilities and directly affects the sociological position of society.